1982
DOI: 10.1007/bf01325512
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the seasonal variation of the most common acute pediatric diseases in the Helsinki area (Finland)

Abstract: Seasonal variations in the incidence of the most common acute diseases in childhood during the inter-epidemic year 1978 were investigated using a sample of 7,068 walk-in patients attending. Aurora Hospital, Helsinki. At least seven out of the ten most common diseases were of infectious origin. Generally, boys and the younger groups were affected most often. The clearest seasonal difference in both sexes was observed in patients with gastroenteritis and otitis media. Among boys, there was also a marked fluctuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
(1 reference statement)
1
3
0
Order By: Relevance
“…Two peaks in early February and early August, and two nadirs in May and November were in the simple harmonic regression model for boys and a cyclic pattern of a simple harmonic curve was found for girls with a maximum incidence rate in November. These findings could confirm the impression that males are more susceptible than females to some infectious diseases [19][20][21][22]. Gender differences in disease incidence may provide important clues to the pathogenesis of diseases and further research on this subject should be encouraged.…”
Section: Strengths and Weaknessessupporting
confidence: 71%
“…Two peaks in early February and early August, and two nadirs in May and November were in the simple harmonic regression model for boys and a cyclic pattern of a simple harmonic curve was found for girls with a maximum incidence rate in November. These findings could confirm the impression that males are more susceptible than females to some infectious diseases [19][20][21][22]. Gender differences in disease incidence may provide important clues to the pathogenesis of diseases and further research on this subject should be encouraged.…”
Section: Strengths and Weaknessessupporting
confidence: 71%
“…Since 1995, the data in the register have been compared with those in hospital discharge registers every few years. Currently, 98% of implantations are recorded in the Finnish Arthroplasty Register (Peltola 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Some studies have a shown an association between seasonal variations in incidence and meteorological factors, namely temperature and relative humidity (Kanno et al, 1983 McConnel and Tobias, 1986;Kobayashi and Takaki,1992;Chang and Halfon,1997) and to study mortality (hurray and Lopez, 1997; Kawachi and Kennedy, 1997;Llorca et al, 1998). Lee (1996) proposed the use of the countries (Nakamura et al, 1998;Peltola, 1982;Sumi, 1998). Therefore, we introduced (max/min) value was also very high.…”
Section: Features Of the Cumulative Percentage Curves For Different Pmentioning
confidence: 99%